Effect of Footfall Induced Vibration on Flat Plate Slabs - Hao Aw, Jia; Han Ng, Wei; Leong Lau, Teck; Jaganathan,, Jayaprakash; Parvez Anwar, Mohammed; Elleithy, Wael (International Journal of Engineering and Technology, 2018)
In recent years, vibration in structures is becoming an increased concern due to the adoption of slender flooring systems (i.e. lighter, thinner and longer floors). Vibrations induced by footfall are more significant in slender floors and should therefore be taken into consideration in the serviceability of the reinforced concrete structures. Limited research exists in the literature focusing on dynamic analysis of flat plate slabs subjected to footfall induced vibration. Hence, this study attempts to breach this research gap by exploring a wider area through conducting a parametric investigation on the effect of floor span, floor aspect ratio, slab thickness and location of openings on the dynamic response of flat plate slabs. Structures are initially designed in accordance with Eurocode 2. Models are generated and analysed using the finite element method and dynamic responses from the footfall analysis are obtained. It was found that vertical displacement increases exponentially with the increase of floor width, aspect ratio and number of openings. However, the displacement decreases with the increase of slab thickness.Â  Moreover, the location of openings is found to have significant effect on the responses of flat plate slabs.Â Â